2017
DOI: 10.1016/j.psychres.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Substantiated childhood maltreatment and young adulthood cannabis use disorders: A pre-birth cohort study

Abstract: This study investigates the association between exposure to prospectively-substantiated childhood maltreatment between 0 to 14 years of age and lifetime cannabis use, abuse and dependence reported at 21 years. Data were taken from 2526 (51.6% female) participants in the Mater Hospital-University of Queensland Study of Pregnancy, a pre-birth, prospective, cohort study. Prospectively-substantiated cases of childhood maltreatment, reported to the government child protection agencies between 0 and 14 years of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 83 publications
2
28
0
Order By: Relevance
“…Physical abuse positively predicted current use of cannabis which is comparable to previous studies [ 36 , 37 ]. In a cohort study conducted by Alemu and colleagues, exposure to physical abuse was found to predict cannabis dependence (AOR = 2.81).…”
Section: Discussionsupporting
confidence: 89%
“…Physical abuse positively predicted current use of cannabis which is comparable to previous studies [ 36 , 37 ]. In a cohort study conducted by Alemu and colleagues, exposure to physical abuse was found to predict cannabis dependence (AOR = 2.81).…”
Section: Discussionsupporting
confidence: 89%
“…One possible explanation for this is that neglect tends to be difficult to define and is poorly reported and often misunderstood as a form of violence, especially in children. Indeed, we found only four studies that evaluated this type of trauma (Abajobir et al, ; Dube et al, ; Huang et al, ; Wilson and Widom, ), which corroborate the observation that neglect does not have a consistent and universally accepted definition (Friedman and Billick, ).…”
Section: Discussionsupporting
confidence: 86%
“…Initial screenings of the titles and abstracts of these studies revealed that 937 papers did not meet the study criteria and duplication was also present in an additional 74 papers (they did not match the thematic criteria). The remaining 34 articles were read, and after applying the criteria for inclusion and exclusion, we selected nine articles for analysis (Abajobir et al, ; Dube et al, ; Fergusson et al, ; Hayatbakhsh et al, , ; Huang et al, ; Rogosch et al, ; Van der Pol et al, ; Wilson and Widom, ). After an indepth review of the reference lists of the nine selected papers, we identified an additional paper (Silverman et al, ) that was also included.…”
Section: Resultsmentioning
confidence: 99%
“…A further limitation is that most work has considered maltreatment as a whole, or focused on physical and sexual abuse. However, there is growing evidence of the adverse psychological effects of emotional abuse and neglect [10][11][12][13][14][15]. Both may alter the development of brain reward and oxytocin systems in children leading, in turn, to poorer care for the subsequent generation when these individuals become parents themselves [16,17].…”
Section: Introductionmentioning
confidence: 99%